Peningkatan Sarana Pembelajaran Daring Dengan Optimalisasi Penggunaan Video Editing Di SMPIT Annida - Rosalina Rosalina; Genta Sahuri; Chong Min An; Rila Mandala (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The advantage of video media in education is that it can boost students' interest in the subject matter by allowing them to watch and hear. Teachers are expected to be able to develop engaging learning materials that encourage students to participate actively in their education. This PkM activity was completed at SMPIT Annida as an activity partner. The issues that were identified were 1) The teacher's ability to self-produce learning media, particularly in making learning videos, 2) The availability of free software that could be used to produce video learning media, but never utilized by teachers, and 3) the improvement process for teaching and learning that is effective, efficient, and more engaging. The focus of this activity was on the instructors and students.